Evaluation of Banking Performance of the Balkan Countries in Type-2 Neutrosophic Fuzzy Environment - Durmuş, Cem Niyazi; Çanakçıoğlu, Mustafa; Topak, Mehmet Sabri; Gorcun, Omer Faruk (Journal of Intelligent Decision Making and Information Science, 2025)
This paper proposes the PSI & CODAS integrated model based on the Type-2 Neutrosophic Fuzzy Numbers (T2fNNs) to solve the decision-making problems encountered in banking and make performance analyses of banking institutions. The proposed model is also an integrated MCDM approach that can overcome many complex situations and many misevaluations by decision-makers. Besides, it provides an applicable and stable assessment, as it is not sensitive to the number of criteria and decision alternatives. The T2NN MCDM approach was applied to evaluate the banking performances of banks in Balkan countries after the COVID-19 global pandemic and demonstrate the implementation of the suggested model. Next, a comprehensive robustness check consisting of two stages was performed to test the validation of the suggested MCDM model and its results. According to the study results, A13 Türkiye İş Bankası was the best option for applying the proposed model and has remained the best option for all scenarios. Besides, minor alterations have been surveyed that did not alter the overall conclusions in the ranking performance of a few options. The sensitivity analysis results prove that the proposed PSI & CODAS approach is a powerful and applicable computational tool, and its results are reasonable, realistic, and substantially accurate.